B) After 2 months he owed

A2= 8500(1.01)^2

Now, in the 3rd month, he has to start his repayments, so far the loan was just building up

Let his monthly repayment be M

After 3 months he owes:

A3= A2*(1.01) - M

= 8500*(1.01)^3 - M

After 4 months:

A4= (8500*(1.01)^3 - M)*(1.01) -M

= 8500*(1.01)^4 - M*(1.01 + 1)

Hence you can see a pattern forming, so for the 60th month:

A60= 8500*(1.01)^60 - M*(1.01^57 + 1.01^56 + ....... + 1)

In the 60th month, the loan should be paid off:

A60= 0

Therefore,

8500*(1.01)^60 - M*(1.01^57 + 1.01^56 + ....... + 1) =0

**(1.01^57 + 1.01^56 + ....... + 1) **is a series.

now all you have to do is find the sum of the series and do a little rearranging and you get the answer

M= 197.745